Avaliação dos mecanismos de adsorção e precipitação do ácido aminofosfônico na ausência de rochas. - Ozório, Renan Galvão (2017)
In the production life of a petroleum well, depletion of the reservoir’s natural pressure is something common to happen even before the point of having no hydrocarbons left to extract has been reached. As a way to reduce this decreasing production tendency, secondary recovery methods are used, such as waterflooding, one of the most applied techniques. In offshore zones, mainly, it is nothing uncommon to see seawater been used as injection fluid. However, as there are advantages in this technique, such as the reduction of logistic costs, there are disadvantages, such as salt precipitations, commonly known as incrustations, caused when the seawater gets in contact with formation water. These incrustations may cause damage to the formation near the wellbore or even block production lines. To combat this phenomenon, the inhibitor squeeze technique is requested. In this procedure, inhibitor is injected in the reservoir hoping to stop the occurrence of incrustations, acting either by precipitation or adsorption mechanism. This work aims to obtain clear visualization of both mechanisms separately, using as base of comparison previous retentions curves obtained by other authors. Additionally, in order to verify the ability of the UV-Visible Spectrophotometer technique in indirect tracking of inhibitor concentration after equilibrium period, batch tests using the inhibitor were conducted without the presence of any kind of rock. The experiments were performed varying the inhibitor, aminotrismethylenephosphonic acid (NTMP), concentration in a 1M solution of NaCl, under two different temperatures, 25 and 70 ºC, and two pHs, 4 and 7. It was assumed 48 hours as the equilibrium time. Finally, the achievement of the same precipitation isotherm was tried through literature review. However, the review showed to be insufficient to bring with more detail a clear visualization of the separated mechanisms and thus the precipitation isotherm, since under the most field operation conditions there is the presence of both phenomenon, being them also dependent of other variables not considered in this work, such as rock formation composition in which the anti-scale is put to act on. It was also noticed that the UV-Visible Spectrophotometer technique presents not enough sensitivity to detect the presence of NTMP in the studied conditions. The negative results of both analytical methods proposed led to an incapacity of comparison between them.